Embodiment and sense-making in autism - De Jaegher, Hanne (Frontiers in Integrative Neuroscience, 2013)
In this article, I sketch an enactive account of autism. For the enactive approach to cognition, embodiment, experience, and social interaction are fundamental to understanding mind and subjectivity. Enaction defines cognition as sense-making: the way cognitive agents meaningfully connect with their world, based on their needs and goals as self-organizing, self-maintaining, embodied agents. In the social realm, the interactive coordination of embodied sense-making activities with others lets us participate in each other's sense-making (social understanding = participatory sense-making). The enactive approach provides new concepts to overcome the problems of traditional functionalist accounts of autism, which can only give a piecemeal and disintegrated view because they consider cognition, communication, and perception separately, do not take embodied into account, and are methodologically individualistic. Applying the concepts of enaction to autism, I show: How embodiment and sense-making connect, i.e., how autistic particularities of moving, perceiving, and emoting relate to how people with autism make sense of their world. For instance, restricted interests or preference for detail will have certain sensorimotor correlates, as well as specific meaning for autistic people. That reduced flexibility in interactional coordination correlates with difficulties in participatory sense-making. At the same time, seemingly irrelevant “autistic behaviors” can be quite attuned to the interactive context. I illustrate this complexity in the case of echolalia. An enactive account of autism starts from the embodiment, experience, and social interactions of autistic people. Enaction brings together the sensorimotor, cognitive, social, experiential, and affective aspects of autism in a coherent framework based on a complex non-linear multi-causality. This foundation allows to build new bridges between autistic people and their often non-autistic context, and to improve quality of life prospects.